SHARIA PUBLIC RELATIONS: BUILDING REPUTATION AND PUBLIC TRUST FOR ISLAMIC FINANCIAL INSTITUTIONS IN INDONESIA - Syarifuddin, Syarifuddin; Salim, Hana; Ali, Ahmed (World Psychology, 2025)
The rapid growth of Islamic Financial Institutions (IFIs) in Indonesia has intensified the need for effective reputation management that aligns with Islamic principles. Conventional Public Relations (PR) models often fall short in communicating the unique ethical value proposition of Sharia-compliant entities, leading to challenges in building deep-rooted public trust. This research aims to conceptualize and propose a “Sharia Public Relations” framework specifically designed for IFIs in the Indonesian context. Employing a qualitative methodology with a multi-case study approach, this study involved in-depth interviews with PR practitioners from leading IFIs, Sharia scholars, and communication experts. The findings reveal that an effective Sharia PR model is grounded in the core principles of siddiq (truthfulness), amanah (trustworthiness), tabligh (communicating transparently), and fathanah (professional wisdom). This framework prioritizes ethical stakeholder engagement, transparent communication of both opportunities and risks, and community-centric initiatives over conventional corporate social responsibility. This study concludes that the implementation of a dedicated Sharia PR model enables IFIs to authentically build reputation and public trust, moving beyond mere compliance to embody Islamic values in their public engagement, thereby creating a sustainable competitive advantage.